THE CORRELATION BETWEEN INTEREST RATES, EXCHANGE RATES, AND CRUDE OIL PRICE VOLATILITY ON IMPORTING-EXPORTING MARKET RETURNS - Benita, Rahma Tri (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose The instability of the market impacts the countries that export and import oil due to the fluctuations in crude oil prices are important to analyze. The fluctuating crude oil prices, are influenced by the unpredictable relationship between supply and demand for the world's oil needs. The rise in oil prices results in an economic deceleration for oil-importing countries that rely heavily on global oil needs. Conversely, low global oil prices can hinder economic development and induce instability in oil-exporting countries. The objective of this research is to predict the close correlation between movements in crude oil prices and capital market returns utilizing various nation characteristics methodologies, particularly as oil importers and exporters. Design/methodology/approach The relationship between capital market returns and oil prices has been examined using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH). Findings Indonesia has quite strong independence compared to other countries because Indonesia has a diversification strategy, is rich in natural resources, and has support for domestic oil needs. Research findings indicate that the volatility in global oil price changes affects different countries in diverse ways. Numerous factors influence capital market returns, extending beyond oil price volatility to encompass political stability, natural resource wealth, global economic conditions, and a nation's fiscal and monetary policies. Research limitations/implications Limitations of the sample used in the study may affect the results of the study and make it difficult to make accurate generalizations. Originality/value This gap analysis result is to look at the identification of findings on what economic factors are most important in influencing returns other than changes in oil prices. So that it can develop inclusive strategies in capital market development to achieve optimal returns.